Stateful Full Adder Using Silicon Diodes - Jaemin Son; Juhee Jeon; Kyoungah Cho; Sangsig Kim (Advanced Intelligent Systems)
Stateful logic can perform logic operations and simultaneously stores computational results in memory devices. Most stateful logic bases and algorithms have been studied using resistive random‐access memory devices. Herein, stateful full adders consisting of silicon p+–n–p–n+ diodes that exhibit switching and memory functions through band modulation are demonstrated. A 1‐bit full adder using ten diodes operates with ten sequential steps of material implication and NOR logic operations, and its energy consumption per operation is 50.4 pJ. Row and column logic operations in a diode crossbar structure enable an N‐bit full adder algorithm. This study demonstrates the feasibility of achieving fully functional in‐memory computations using silicon diodes.